Ethnocultural Landscape of Medieval Mausoleums in the Volga-Urals - Ivanov V.A. (Золотоордынское обозрение)
The purpose of the study: To show that the Golden Horde mausoleums (keshene) of the Southern Cis-Urals – Husein-bek, Tura Khan, Bendebike, Kesene (Tamerlane’s Tower) – belong not only to different architectural schools, but they also belong to different ethnocultural and geographical spaces. In this regard, the following tasks were laid out: To show that the Keshene Bendebike and the “Tower of Tamerlane” belong to a large group of so-called. steppe brick mausoleums built in the steppes of the Volga and Southern Urals according to the canons of the Central Asian architectural school. Erected in the second half to the end of the 14th century (or even at the beginning of the 15th century), they were intended to perpetuate the memory of representatives of the elite of the Golden Horde nomads. Unlike the brick ones, the stone mausoleums-keshene of Husein-bek, Tura Khan, Small Keshene were built according to the traditions of Bulgarian architecture in the forest-steppe regions of the Dema River valley, a territory inhabited in the 14th century, by carriers of the Chiyalik culture. Research materials: The study uses geographical, archaeological, and folklore data on the kashene mausoleums of the Southern Cis-Urals obtained by researchers of the 18th–20th centuries. Results and scientific novelty: The geography of the distribution of brick mausoleums in the steppes of the Volga and Cis-Ural regions shows that, based on the time of their construction, they could have appeared among the Golden Horde nomads even at a time when paganism was not completely supplanted by Islam (there are numerous nomadic burials with coins of Uzbekistan and later rulers). Thus, mausoleums erected over the graves of the nomadic elite became an organic part of the culture of the nomads of the Golden Horde. The stone mausoleums of the Cis-Urals had nothing to do with nomadic culture. They were built in the ethnocultural space and on the territory of settlement of semi-nomadic carriers of the Chiyalik culture (Ishtyak-Ugrians). They became centers of Muslim cemeteries quite late – not earlier than the 17th century – when the “Chiyaliks” were already assimilated by the Turkic ancestors of the Dem Bashkir-Mings/Mings. Therefore, in the historical memory of their descendants, the Bashkirs of the 18th–19th centuries, the stone keshenes of Husein-bek and Tura Khan were overgrown with traditions and legends, the plots and characters of which are not directly related to the ethnocultural history of the Bashkirs.